Bridging the Time Gap: A Copper/Zinc Oxide/Aluminum Oxide Catalyst for Methanol Synthesis Studied under Industrially Relevant Conditions and Time Scales. Issue 41 (8th September 2016) - Lunkenbein, Thomas; Girgsdies, Frank; Kandemir, Timur; Thomas, Nygil; Behrens, Malte; Schlögl, Robert; Frei, Elias
Abstract: Long‐term stability of catalysts is an important factor in the chemical industry. This factor is often underestimated in academic testing methods, which may lead to a time gap in the field of catalytic research. The deactivation behavior of an industrially relevant Cu/ZnO/Al2 O3 catalyst for the synthesis of methanol is reported over a period of 148 days time‐on‐stream (TOS). The process was investigated by a combination of quasi in situ and ex situ analysis techniques. The results show that ZnO is the most dynamic species in the catalyst, whereas only slight changes can be observed in the Cu nanoparticles. Thus, the deactivation of this catalyst is driven by the changes in the ZnO moieties. Our findings indicate that methanol synthesis is an interfacially mediated process between Cu and ZnO. Abstract : ZnO is the key for stability : Long‐term stability tests of catalysts are often underestimated in academia, despite industrial requirements. The deactivation of an industrially relevant Cu/ZnO/Al2 O3 catalyst for the synthesis of methanol was investigated over a period of 148 days time‐on‐stream, with a combination of quasi in situ and ex situ analysis techniques. The findings indicate that controlling the polymorphism of ZnO is the key to the stability of the investigated catalytic system.